Vai trò của chuyển đổi số đối với tăng trưởng kinh tế vùng Đông Nam Bộ - Nguyễn Lê Hoàng Thụy Tố, Quyên; Đặng Thị Ngọc, Thế (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
The study employs a combination of classical and modern economic growth theories to assess the impact of digital transformation on growth in the Southeast region. Using secondary data over the 2005–2021 period of 6 provinces and cities in the Southeast Region and pooled mean group (PMG) regression method, the research results provide evidence of a statistically positive effect of digital transformation (measured by the ICT index) on the growth of the Region. Besides, the roles of foreign direct investment and human capital have also been confirmed in the growth model. An interesting finding of the study is that institutions measured in terms of either private economic development policy or business support services have no significant impact on growth as expected.